Advancements in hydrogel technology for ocular drug delivery - Doanh Truong; Kevin Y. Wu; Louis Nguyen; Simon D. Tran (Exploration of BioMat-X, 2024)
Hydrogel-based drug delivery systems (DDS) offer promising alternatives for treating ocular diseases by overcoming the limitations of traditional therapies, such as low bioavailability, frequent administration, and invasiveness. Hydrogels, with their high biocompatibility and ability to respond to external stimuli, can provide sustained and targeted drug delivery. This review highlights the unique properties of hydrogels, including their swelling behavior, porosity, and mechanical strength, making them suitable for various ocular applications. The classification of hydrogels based on cross-linking methods, origins, and stimuli responsiveness is discussed, emphasizing their potential in drug delivery for dry eye disease (DED), glaucoma, corneal alkali burns, and neovascularization. Notable advances include thermosensitive and pH-responsive hydrogels, which have shown promising results in preclinical studies. Despite these advances, most studies are still in preclinical stages, highlighting the need for rigorous human trials to validate the safety and efficacy of hydrogel DDS. Collaborative efforts among researchers, pharmacologists, and ophthalmologists are essential to translating these innovations into clinical practice, ultimately improving patient outcomes in ocular disease management.